Bad Things Come to Those Who Do Not Wait: Temporal Discounting Is Associated With Compulsive Overeating, Eating Disorder Psychopathology and Food Addiction - Kekic, Maria; McClelland, Jessica; Bartholdy, Savani; Chamali, Rifka; Campbell, Iain C.; Schmidt, Ulrike (Frontiers in Psychiatry, 2020)
The tendency to act on immediate pleasure-driven desires, due to the devaluation of future rewards (a process known as temporal discounting; TD), has been associated with substance use disorders (SUD) and with conditions characterised by compulsive overeating. Using a large inclusive sample, we examined whether TD was related to compulsive overeating and associated problems. Participants (N = 432, [48 males]) completed an online survey, which included a hypothetical monetary TD task, the Yale Food Addiction Scale (YFAS), the Eating Disorder Examination-Questionnaire (EDEQ), and the Depression Anxiety and Stress Scales (DASS). TD correlated with frequency of compulsive overeating and compensatory behaviours, with severity of food addiction, with eating disorder psychopathology, and with body mass index (BMI). As elevated rates of TD are associated with a range of behaviours/measures, it can be proposed that it is more likely that elevated TD rates are a predisposing factor rather than a consequence of the behaviour ie elevated rates of TD contribute to pathological eating-related behaviours. Future research should seek to confirm these findings and investigate whether interventions aimed at reducing TD have clinical potential for treating problematic eating behaviours.